Assessment of cataract and glaucoma knowledge, attitudes, and practices among students at the University of Mbandaka, Democratic Republic of the Congo - Babundo Kabu Eanga , Yvon; Mazoba, Tacite Kpanya; Lubeji Kayembe, David (Orapuh Journal, 2025)
Introduction Glaucoma is a progressive optic neuropathy characterized by optic disc excavation and visual field loss, primarily due to elevated intraocular pressure. The knowledge, attitudes, and practices of the population regarding cataract are essential in strategies for blindness prevention and control. Purpose This study was carried out to assess the knowledge, attitudes, and practices related to cataract and glaucoma among students of the University of Mbandaka in DR Congo. Methods This was a cross-sectional descriptive and analytical study. Data were collected using an interview-administered questionnaire on cataract and glaucoma from 15 August to 15 November 2023. Out of 4,012 students admitted (2022–2023), 645 students agreed to participate and responded to a pre-tested structured questionnaire through face-to-face interviews. Data were entered into Excel 2010 and exported to SPSS version 21. The level of statistical significance was set at p < .05. Results Among the 645 respondents, 67.6% were men (sex ratio M/F: 2:1). The mean age of respondents was 27.4 ± 9.5 years (min–max: 18–56 years; median: 23 years). A large proportion of the respondents (60%) had good knowledge about cataract (definition, type, information); however, their knowledge about cataract complications and treatment was poor. Similarly, 60% of respondents had good knowledge about glaucoma (definition, type, information). However, a significant portion of participants had poor knowledge of glaucoma treatment (53%), lesion site (51.8%), complications (50%), and definition (37.9%). The following variables—male students, students from the medical school, and students in B2 bachelor and law faculties—were significantly associated with good knowledge of cataract and glaucoma. Conclusion We believe that eye care providers should make use of the good level of knowledge among students of the University of Mbandaka when planning health education campaigns related to cataract and glaucoma, as well as activities for blindness prevention in the province of Equateur.